2013
DOI: 10.1186/1743-422x-10-225
|View full text |Cite
|
Sign up to set email alerts
|

Systemic varicella-zoster virus infection in two critically ill patients in an intensive care unit

Abstract: Varicella-zoster virus (VZV) usually causes localized zoster in adults. However, in immunocompromised patients, it can cause systemic infection accompanied by complications such as pneumonia, encephalitis, and hepatitis. Although most of critically ill patients in intensive care unit (ICU) are immunologically compromised, they are usually not considered to be at risk for systemic VZV infection.We report two cases of systemic VZV infection occurring in critically ill patients in an ICU. One patient was a 69-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Till now, only a few cases of herpes zoster-associated acute pancreatitis have been reported; among them, most involve immunocompromised individuals, such as those in intensive care, AIDS patients, or receiving long-term immunosuppression, such as recipients of stem cell, renal or liver transplants [5][6][7][8][9]. There were only a handful of studies which reported acute pancreatitis associated with VZV in children with chickenpox and one study reported an elderly patient with herpes zoster suffering from systemic complications, including pancreatitis and encephalitis [10][11][12]13].…”
Section: Discussionmentioning
confidence: 99%
“…Till now, only a few cases of herpes zoster-associated acute pancreatitis have been reported; among them, most involve immunocompromised individuals, such as those in intensive care, AIDS patients, or receiving long-term immunosuppression, such as recipients of stem cell, renal or liver transplants [5][6][7][8][9]. There were only a handful of studies which reported acute pancreatitis associated with VZV in children with chickenpox and one study reported an elderly patient with herpes zoster suffering from systemic complications, including pancreatitis and encephalitis [10][11][12]13].…”
Section: Discussionmentioning
confidence: 99%
“…Toxicities associated with acyclovir, which are often dose dependent, remain significant and may be exacerbated in immunocompromised patients with underlying renal dysfunction. The duration of therapy should be 14 days; however, 21 days should be strongly considered in patients with underlying immunocompromise 36,92,93. Use of oral agents such as valacyclovir has not been studied and cannot be recommended at this time.…”
Section: Management Of Cns Viral Diseasementioning
confidence: 99%
“…By contrast, in disseminated zoster, a rare manifestation of reactivated latent VZV, the systemic distribution of vesicular eruptions and systemic dissemination of the pathogen to many other organs occurs. Disseminated zoster is rarely seen in immunocompetent patients, but has been reported in immunocompromised patients such as those who have undergone hematopoietic stem cell transplantation and solid organ transplantation, or who have lymphoma or acquired immune deficiency syndrome (AIDS) [6].…”
Section: Discussionmentioning
confidence: 99%
“…We administered 500 mg of acyclovir as high-dose acyclovir therapy. Intravenous immunoglobulin has also been reported to be a treatment option [6, 10]. VZV vaccination cannot be used as a preventative in immunocompromised patients, because the VZV vaccine is a live-virus vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation